PERGULATAN IMAN BUDHI SANTOSA UNTUK MENCAPAI POSISI TERKONSEKRASI DALAM ARENA SASTRA YOGYAKARTA - Anggun Nirmala Safitri (POETIKA, 2015)
This article tries to uncover the strug gle of  Iman Budhi Santosa to reach the dominant position in the field of  Yogyakarta literature. Bourdieu’s theor y, the field of  cultural production, is used to uncover the relation between objects that support Iman to become a consecrated poet in the field of  Yogyakarta literature. The relation of  the objects are explained by the concepts of  habitus, capital, strategy, practice, trajectory.Literary practices which are manifestated in the form of  literary writing and publishing activities, the participation in literary activities, institution forming in Yogyakarta are accumulated as symbolic capital which directs his possition to become a consecrated poet in Yogyakarta.Keywords: Iman Budhi Santosa, Bourdieu, the field of  cultural production, habitus, capital, strategy, practice, trajector y